Comparison of radiation shielding ability of Bi2O3 micro and nanoparticles for radiation shields. (November 2022) - Almuqrin, Aljawhara H.; Sayyed, M.I.; Elsafi, M.; Khandaker, Mayeen Uddin
Abstract: We reported the radiation attenuation ability of Bi2 O3 powder in different sizes. We measured the linear attenuation coefficient for the two investigated Bi2 O3 samples using a narrow collimated beam method. A HPGe detector was used to report the number of photons that can penetrate the samples and the energies of the photons was selected in the energy range of 0.0595 up to 1.408 MeV. The LAC for the Bi2 O3 in micro size is relatively higher than that for the sample with nano- Bi2 O3 if the two samples have the same volume, and the difference between the LAC for the two samples is 33.4% at 0.059 MeV, while it is 29.8% at 0.081 MeV. The mass and thickness ((M1/2 and H1/2 ) needed to shield the intensity of the initial photon to its half value were also reported. The results demonstrated that if we have two different sizes of Bi2 O3 with the same masses, we need lighter sample of Bi2 O3 nanoparticles to reduce 50% of the incoming photons in comparison with the micro Bi2 O3 Highlights: The radiation attenuation ability of Bi2 O3 powder in different sizes was reported. The nano sample has highest attenuation than the micro in all the studied energies. The LAC is 2.76 cm −1 for SR-micro Bi2 O3 and 3.55 cm −1 for SR-nano Bi2 O3 at 0.060 MeV.